ASSESSING BEHAVIORAL COMPATIBILITY BETWEEN SHELTER DOGS AND POTENTIAL ADOPTERS - Sorin Marian Mârza; Felix Daniel Lucaci; Mélanie Campanico Galego (Agricultura, 2025)
Ensuring a successful match between shelter dogs and adopters is a key factor in promoting long-term pet ownership and reducing return rates. This study explored the compatibility between behavioral profiles of 49 dogs, assessed via the C-BARQ questionnaire, and demographic and lifestyle profiles of 78 potential adopters. The research was conducted in partnership with two shelters: SVPA in Switzerland and NUCA in Romania. Results indicated that most shelter dogs were excitable but non-aggressive, and adopters were predominantly young, empathetic, and experienced with pets. Active adopters tended to be more compatible with excitable dogs, whereas calmer home environments better suited anxious or fearful dogs. These findings support the use of standardized behavioral assessments and adopter profiling tools to improve adoption outcomes and animal welfare.